Pseudoaneurysm associated haemosuccus pancreaticus - a rare and dangerous disease - Julia Wagenpfeil; Daniel Kütting; Christian P. Strassburg; Carsten Meyer (CVIR Endovascular, 2020)
Abstract Background In patients with upper gastrointestinal bleeding and hemorrhage originating from the major duodenal papilla pseudoaneurysm associated haemosuccus pancreaticus (HP) is a rare differential diagnosis which should be considered. Diagnosis may be challenging, as clinical presentation is often unspecific with only intermittent hemorrhage. Treatment of the causal pseudoaneurysm is mandatory and endovascular coil embolization is the suitable first-line management strategy. Until now there are only a very few studies about this clinical picture and its therapeutic options, especially data regarding whether additional fluid embolization is beneficial/necessary in HP is currently lacking. Case presentation We report a case of a 59-year-old male patient with chronic pancreatitis and haemosuccus pancreaticus caused by a pancreatico-arterial fistula with an associated inflammatory pseudoaneurysm of the splenic artery. Initially we sought to embolize the pseudoaneurysm with microcoils. As only one coil could be safely deployed in the pseudoaneurysm we additionally employed tissue adhesive embolization in order to achieve complete occlusion of the pseudoaneurysm as well as the pancretico-arterial fistula. In the presented case inflammatory levels decreased following embolization, possibly linked to a decline in pathologic excretion of elastase and autodigestion. As not only the pseudoaneurysm but also the underlying fistula were occluded, the risk of recurrence may conceivably be reduced. Conclusions Diagnosis of HP is difficult and treatment of the causal pseudoaneurysm is mandatory. Endovascular embolization is the suitable first-line management strategy, complete occlusion of the fistula should be considered when possible.